The use of technology in music education in North Cyprus according to student music teachers - Gorgoretti, Basak (Education Assoc South Africa, 2019)
Today, the rapid changes and developments in information and communication technologies affect all sectors, which includes a positive impact in the field of education. For this reason, it is important that teachers make effective use of technologies and keep up with innovation to meet the needs of the new generation. This research focuses on describing technology use in music education at a university in North Cyprus, according to 18 student music teachers, to highlight the extent to which technology has been integrated into music education, making recommendations for further integration. This mixed-methods study employed a questionnaire containing closed-ended questions, which were analysed quantitatively, as well as open-ended questions, which were analysed based on content analysis. Results underline the importance of curriculum updates to integrate information and communication technology into student music teacher training and the need for in-service training to keep established teachers up-to-date with innovative technologies. Future research is recommended to compare music education practices cross-culturally and to identify ways of maximising the benefits of innovations in technology for music educators.
Keywords: information-communication technology (ICT); music technology; social media; student music teacher